2023
DOI: 10.3390/ma16030951
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Short-Pulse Microwave Radiation on Thermochemical Properties Aluminum Micropowder

Abstract: The thermochemical properties of Al micropowder after exposure to microwave irradiation were investigated. The Al micropowder was exposed to microwave irradiation in air with a frequency of 2.85 GHz, a power density of 8 W/cm2, and a pulse duration of 25 ns and 3 µs. The thermochemical parameters of the irradiated metal powders were determined by the method of thermal analysis at the heating in air. It was found that an increase in the duration of microwave pulses and irradiation time leads to the thermal anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Shang et al [57] demonstrated, in their study, powder mixtures based on magnesium hydride with doping of 8 mol% aluminum, nickel, iron, titanium, copper, and niobium. According to the results, the heat of the formation obtained during thermally stimulated desorption was at 300 • C, and the MgH 2 -8 mol% Al system had a heat of formation −28.36 kJ/mol, compared to magnesium hydride −75.99 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shang et al [57] demonstrated, in their study, powder mixtures based on magnesium hydride with doping of 8 mol% aluminum, nickel, iron, titanium, copper, and niobium. According to the results, the heat of the formation obtained during thermally stimulated desorption was at 300 • C, and the MgH 2 -8 mol% Al system had a heat of formation −28.36 kJ/mol, compared to magnesium hydride −75.99 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%
“…The same was carried out in this study-nano-sized aluminum powder produced by the method of the electric explosion of wires (EEW) was used and its effect on the hydrogen yield temperature from the composite was determined. In this work, EEW-aluminum powder obtained on the basis of the Tomsk Polytechnic University acts as such an additive [56,57]. The EEW method for producing nanoscale powders, in fact, combines the characteristics of dispersing methods-the destruction of the conductor under the action of electricity and methods of vaporization and condensation-and most of the material of the conductor during the electric pulse explosion passes into the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…The same was carried out in this study -nanosized aluminum powder produced by the method of electric explosion of wires (EEW) was used and its effect on the hydrogen yield temperature from the composite was determined. In this work, EEW-aluminum powder obtained on the basis of Tomsk Polytechnic University acts as such an additive [56][57]. The EEW method for producing nanopowders, in fact, combines the characteristics of dispersing methods -destruction of the conductor under the action of electricity and methods of vaporization and condensation -most of the material of the conductor during the electric pulse explosion passes into the gas phase.…”
Section: Introductionmentioning
confidence: 99%